PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN PRASARANA LINGKUNGAN PADA PROGRAM PLPBK DI KELURAHAN TAMBAKREJO, KOTA SEMARANG - Dyah Putri Makhmudi; Mohammad Muktiali (Jurnal Pengembangan Kota, 2018)
Participation is the participation of a person in a social group to take part of existing community activities, outside of their work. Community participation is needed in a development program because the success of the program is related to community participation in running the program. Tambakrejo village became one of the villages that run the PLPBK program in Semarang City because of a good achievement from BKM. The purpose of this study was to determine community participation in the development of environmental infrastructure in the PLPBK program in Tambakrejo Village. The quantitative approach was used in this study by distributing 87 questionnaires and conducting interviews, observation and document review. Forms of participation given by society such as money, goods, energy and thoughts. The level of community participation is at the level of notification, meaning that in the development of environmental infrastructure in the PLPBK program there is a provision of information to the public. The sustainability of the PLPBK program in Tambakrejo Village is closely related to the level of community participation and the role of the parties involved in implementing the PLPBK Program.